Genome-wide association studies in suicidology — analysis of main results - V. A. Rozanov; G. E. Mazo; N. A. Kulemin; A. Yu. Gorbachev; E. D. Kasyanov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2019)
Studies of suicide genetics can be divided into 3 periods: 1) period of classical methods of behavioral genetics; 2) candidate genes association studies, and 3) genome-wide association studies. The majority of studies using candidate genes strategy has been dedicated to main neurotransmitter systems (serotonine, catecholamines, GABA, excitatory aminoacids system, etc.) and in the last decade — to genes of the stress-reactivity system and neurotrophins. On the other hand among main GWAS findings are genes that are involved in neurodevelopment, neuroplasticity, cell adhesion and migration, proliferation and intracellular signaling, as well as immune system functions. We consider it a confirmation of the relevance of the stressvulnerability models that imply key role of the early development and involvement of the neuroplasticity, as well as models that focus on stress as a systemic reaction of the organism in pathogenesis of suicidal behavior. It should be noted that findings of different GWAS studies most often do not coincide and in general produce rather heterogeneous picture. It may be due to differing bioinformatics approaches, phenotypes description differences and study design peculiarities. We consider that more research is needed in all three directions with involvement of NGS approaches, in particular whole-exome sequencing.